2015
DOI: 10.1155/2015/385023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Doses of Levofloxacin on Antioxidant Defense Systems and Markers of Renal and Hepatic Dysfunctions in Rats

Abstract: Levofloxacin (LFX) is a broad spectrum fluoroquinolone antibiotic used in the treatment of infections such as pneumonia, chronic bronchitis, and sinusitis. The present study assessed the likely toxic effect of LFX on hepatic and renal tissues in rats. Twenty male Wistar rats were randomly divided into four treatment groups: A: control, B: 5 mg/kg bw LFX (half therapeutic dose), C: 10 mg/kg bw LFX (therapeutic dose), and D: 20 mg/kg bw LFX (double therapeutic dose). After seven days of administration, result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
6
10
0
Order By: Relevance
“…Elevated plasma ALT and AST may be linked with membrane leakage of the hepatocyte cytosolic contents which is reflected in significant elevation of the plasma of rats treated with different doses of MXF. This observation is in consonance with previous findings on other fluoroquinolones [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Elevated plasma ALT and AST may be linked with membrane leakage of the hepatocyte cytosolic contents which is reflected in significant elevation of the plasma of rats treated with different doses of MXF. This observation is in consonance with previous findings on other fluoroquinolones [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Depletion of the cell membrane antioxidant system is known to predispose membrane lipids to oxidation leading to accumulation of LPO products [ 58 ] including MDA as observed in this study. Previous studies have reported fluoroquinolone-induced increase in tissue MDA level [ 45 , 59 – 61 ] and lipid peroxides [ 62 ] in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Olayinka et al (19) used variant doses of levofloxacin, they found that after 7 days of administration there were high AST and ALT. They concluded that these changes were due to its effect on the antioxidant defense system by stimulating the oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…[2].When compared to other fluoroquinolones, LFX has a substantially higher efficacy in treating typhoid fever. It's commonly used to treat infections like pneumonia, sinusitis, and genitourinary infections [3]. LFX's bactericidal activity is primarily achieved by its interaction with the enzyme DNA gyrase, which inhibits DNA replication and transcription, preventing bacteria from dividing [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E, as a conventional antioxidant, has been shown to protect the liver from a variety of pollutants [14]. It is a well-known free radical scavenger that protects essential cellular structures from oxidative injury caused by oxygen free radicals and lipid peroxidation reactive products [17].Various antioxidants, such as vitamin C, vitamin E, and selenium, were effectively added to the diet, reducing oxidative stress in vivo and in animal products [3,18,19].…”
Section: Introductionmentioning
confidence: 99%